EMDR as Treatment Option for Conditions Other Than PTSD: A Systematic Review - Scelles, Charles; Bulnes, Luis Carlo (Frontiers in Psychology, 2021)
Eye Movement Desensitization and Reprocessing (EMDR) is a treatment for post-traumatic stress disorder (PTSD). The technique is known to facilitate reprocessing of maladaptive memories that are thought to be central to this pathology. Here we investigate if EMDR therapy can be used in other conditions. We conducted a systematic literature search on PubMed, ScienceDirect, Scopus, and Web of Science. We searched for published empirical findings on EMDR, excluding those centred on trauma and PTSD, published up to 2020. The results were classified by psychiatric categories. Ninety articles met our research criteria. A positive effect was reported in numerous pathological situations, namely in addictions, somatoform disorders, sexual dysfunction, eating disorders, disorders of adult personality, mood disorders, reaction to severe stress, anxiety disorders, performance anxiety, Obsessive-Compulsive Disorder (OCD), pain, neurodegenerative disorders, mental disorders of childhood and adolescence, and sleep. Some studies reported that EMDR was successful in usually uncooperative (e.g., Dementia) or unproductive cases (e.g., aphasia). Moreover, in some severe medical conditions, when psychological distress was an obstacle, EMDR allowed the continuation of treatment-as-usual. Furthermore, the effects observed in non-pathological situations invite for translational research. Despite a generally positive outlook of EMDR as an alternative treatment option, more methodologically rigorous studies are needed. We discuss the advantages and limitations and possible implications for the hypothesised mechanisms of action